Technical roadmap of ultra-thin crystalline silicon-based bioelectronics - Mingyu Sang; Kyubeen Kim; Doohyun J Lee; Young Uk Cho; Jung Woo Lee; Ki Jun Yu (International Journal of Extreme Manufacturing)
Ultra-thin crystalline silicon stands as a cornerstone material in the foundation of modern micro and nano electronics. Despite the proliferation of various materials including oxide-based, polymer-based, carbon-based, and two-dimensional (2D) materials, crystal silicon continues to maintain its stronghold, owing to its superior functionality, scalability, stability, reliability, and uniformity. Nonetheless, the inherent rigidity of the bulk silicon leads to incompatibility with soft tissues, hindering the utilization amid biomedical applications. Because of such issues, decades of research have enabled successful utilization of various techniques to precisely control the thickness and morphology of silicon layers at the scale of several nanometres. This review provides a comprehensive exploration on the features of ultra-thin single crystalline silicon as a semiconducting material, and its role especially among the frontier of advanced bioelectronics. Key processes that enable the transition of rigid silicon to flexible form factors are exhibited, in accordance with their chronological sequence. The inspected stages span both prior and subsequent to transferring the silicon membrane, categorized respectively as on-wafer manufacturing and rigid-to-soft integration. Extensive guidelines to unlock the full potential of flexible electronics are provided through ordered analysis of each manufacturing procedure, the latest findings of biomedical applications, along with practical perspectives for researchers and manufacturers.